Avaliação de dose de entrada na pele em pacientes pediátricos através de medidas dosimétricas - Oliveira, Ana Luiza da Rosa de (2008)
The great use of examinations of diagnosis for image in children brought the concern with the increasing dose of radiation absorbed in the accomplishment of a radiographic examination. The objective of this research is to carry through evaluation of the practical ones of x-rays in pediatric radiology, aiming at to optimize the radiological rocedures and the production of images with quality for the diagnosis with the lesser dose to the patient. The methodology is based on the accompaniment of pediatric examinations and dosimetry measures through the use of dosemeters TLD and specific software (DoseCal) for the evidence of the reality in a radiology service. Measures of pediatric patients in radiographic examinations of thorax had been carried through in a public hospital in the Curitiba. Groups with different age groups had been formed in the evaluation of routine examinations of thorax in projections AP/PA and LAT, where they are divided in groups of 0-1 year, 1-5 years, 5-10 years and 10-15 years. Part of the carried through examinations had been evaluated with thermoluminescence dosemeters TLD-100 for the collection of the entrance surface dose (ESD). The measured doses are compared with the gotten ones with the DoseCal software, that makes the calculation of dose for each patient from the income of the device of rays X. The ESD is evaluated always that it has diagnostic quality in the radiographic image. The objective is to verify if the minimum requirements had been reached, for a good quality of image and bringing a small dose to the patient, as party to suit of to optimize procedures.